PENGARUH IMUNOMODULASI DARI EKSTRAK Caulerpa lentilifera PADA PROFIL HEMATOLOGI BALB/c - Renanda Baghaz Dzulhamdhani Surya Putra; Ayu Winna Ramadhani; Asus Maizar Suryanto Hertika (Jurnal Perikanan Pantura (JPP), 2023)
Caulerpa lentillifera is widely known to have pharmacological benefits based on a variety of research findings. The study aims to analyze the potential immunostimulant extract of ethanol Caulerpa lentillifera in blood profiles in vivo. The methods carried out included extraction of Caulerpa lentillifera ethanol, observation of the hematological profile of erythrocytes, leukocytes and micronucleus and phagocytosis activity in the Balb/c scavengers administered orally with a dose of 25, 50, 100, 150 mg/kg BW for one week. The results obtained that Caulerpa lentillifera ethanol extract showed a significant increase in the number of leukocytes at each treatment dose. The number of erythrocytes also increased but did not show any significance. The activity of phagocytosis also showed a significant increase with the highest percentage of the treatment dose of 100 mg/kg BW. The results of the micronuclei analysis showed no difference. Based on the results of this study showed an increase in the number of erythrocytes leukocytes as well as phagocytosis indicated the occurrence of an increased immune system. It can be concluded that Caulerpa lentillifera is also able to boost the immune system or as an immunostimulant through increased blood profile as well as phagocytosis activity in vivo.